Redesain Museum Negeri Sulawesi Tenggara dengan Pendekatan Arsitektur Kontemporer - Patilangi, Andi (Innovative: Journal Of Social Science Research, 2024)
The establishment of the Southeast Sulawesi State Museum has been conceived with a contemporary architectural approach to create a space that serves not only as a means of learning and information but also as an educational entertainment venue. The aim of this study is to design a museum building that can respond to contemporary architectural needs and reflect the local identity of Kendari city. The research was carried out using a descriptive method to analyze the qualitative factors influencing architectural design. This method includes data collection through direct observation at the related location and interviews with competent sources, as well as literature review from key sources relevant to the museum's architectural issues. The findings of this study present the physical design of the museum building, emphasizing the contemporary architecture concept while considering its existence and function as a center for learning and entertainment. From this analysis, a design is recommended that not only meets functional needs but also enriches the contemporary architectural perspective of museum buildings in Kendari City. The study concludes that a contemporary architectural approach can be applied in the design of the Southeast Sulawesi State Museum by considering aspects of usability, aesthetics, and connectivity with the surrounding environment, thereby creating a significant cultural and educational landmark for the Southeast Sulawesi community.